Micronutrient deficiency in type 1 and 2 diabetes mellitus: diagnosis and therapy - Nur Rosyid, Fahrun (International Journal of Research in Medical Sciences, 2022)
Diabetes is a group of metabolic diseases characterized by increased blood glucose levels (hyperglycemia) due to decreased insulin secretion and/or activity. Chronic hyperglycemia in diabetics is associated with long-term damage, dysfunction and failure of multiple organs such as the eyes, kidneys, nerves, heart and blood vessels. Micronutrients consist of vitamins and minerals that the body needs in small amounts for cellular metabolism. Micronutrients function as cofactors in enzyme-catalyzed reactions and if they are deficient, they can result in impaired metabolic function that can lead to more serious disease conditions. Micronutrients are beneficial for metabolism, gene expression and influence the development or progression of a chronic disease, including diabetes. Metabolic changes in diabetes are very complex, if not controlled properly can develop into complications such as neuropathy, nephropathy, cardiopathy, dyslipidemia and retinopathy. The micronutrients needed by DM patients are vitamin B complex consisting of B1 (thiamin), B2 (riboflavin, B6 (pyridoxine), B12, niacin, biotin, pentothenic acid, as well as folic acid and vitamin C. Minerals that need to be given as therapy in DM patients namely chromium, magnesium, manganese, selenium, vanadium and zinc.